«Өзі және басқалар» қарым-қатынасындағы антропологиялық әдіснаманы дамыту - Soon-ok, Myong; Byong-soon, Chun; N.B., Yem; N., Aljanova (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2020)
The study examines the shift of perspective on research target and evolution of anthropological theory and methodology since the Enlightenment to the modern times. Anthropologists have contributed to the study of others, with the aim of colonial rule in undeveloped and undifferentiated societies since the time of enlightenment. They have made the mistake of tailoring other cultures from a western perspective. As an alternative for that problem, they have attempted to develop anthropological methodologies such as cultural relativism and insider perspectives. However, in advanced research methods, there is a dilemma of inequality in the relationship between researchers and research targets. In the process of research, the interaction between the researcher and the target influences the research result, and therefore, a device was devised to explore the self, the researcher as a participant of research while studying and writing. As a research method, historical and literature data were examined to reveal the debates that have been turning points from the Enlightenment to the present in the evolution of anthropological methodologies and theories. Key words: anthropological methodology, anthropological theory, fieldwork, ‘self and other’, research methods.